2023
DOI: 10.1108/ohi-09-2022-0238
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sense of place dimensions on visitors' conservation behavioral intention: the case of Semarang Old Town, Indonesia

Abstract: PurposeThe purpose of the study is to confirm the influence of each dimension of visitor's sense of place (place identity, place attachment and place dependence) on each dimension of conservation behavioral intention (general behavioral intention and specific behavioral intention) in the context of urban heritage.Design/methodology/approachThis study uses a quantitative methods. Research respondent is individual visitor who meet the research criteria. The strength influence of sense of place dimension (indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Tuan 1974, a human geography scientist, found that there is an emotional connection between people and their community and their daily life settings that are related with environmental perceptions (Jin, et. al, 2020;Dameria et.al. 2022;Javed & Kour, 2022;Qiu, 2023).…”
Section: Place Attachment (Pa)mentioning
confidence: 98%
See 2 more Smart Citations
“…Tuan 1974, a human geography scientist, found that there is an emotional connection between people and their community and their daily life settings that are related with environmental perceptions (Jin, et. al, 2020;Dameria et.al. 2022;Javed & Kour, 2022;Qiu, 2023).…”
Section: Place Attachment (Pa)mentioning
confidence: 98%
“…So that, inappropriate behaviour at their place is seen offensive to themselves. Place dependence deals with how the place well serves to achieve one's goals compared to another place and it leads them to be loyal., In other words, the ability of the place to satisfy recreational, selfenhancement, or other psychological goals of an individual (McCabe, 1993;Klanica et.al., 2006;Cheng, Wu, Huang, 2013;Tonge et.al., 2015;Alrobaee& Al-Kinani, 2019;Dameria et.al., 2022).…”
Section: Place Attachment (Pa)mentioning
confidence: 99%
See 1 more Smart Citation